Effect of Preparation Parameters on Methylene blue number of Activated Carbons Prepared from a Locally Available Material - Shrestha, Rajeshwar Man (Journal of the Institute of Engineering, 2017)
The adsorption of Methylene blue by the activated carbons prepared from a locally available material Lapsi Seed Stone has been studied. Various activated carbons were prepared by varying the parameters such as ratio of Lapsi seed stone particles to Phosphoric acid, carbonization temperature and carbonization time. Determination of Methylene blue numbers of the activated carbons was done by single point method by batch mode. Methylene blue number is found to be affected by the various preparation conditions like carbonization temperature, carbonization time, ratio of activating agent and Lapsi seed stone particles and the concentration of phosphoric acid. The optimum conditions for the preparation of activated carbon are found to be carbonization temperature 400°C for 4 hours at the ratio of 1:1 Lapsi seed stone particles and Phosphoric acid. Journal of the Institute of Engineering, 2016, 12(1): 169-174